AN ANALYSIS OF ACTIVE ZONES IN NARRATIVE TEXT: A COGNITIVE LINGUISTICS APPROACH - Humaira R Maulidia (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
In this current research, the cognitive linguistics theory by Langacker (1987) describes linguistic as general cognition and thinking is used to maintain interrelations of narrative text with a deep knowledge analysis of the meanings of lexical concepts in it. In addition, this research aimed to find out the entity’s profiles found in two narrative texts and the different active zones found in narrative texts. The active zone is cognitive operations in cognitive linguistics that deal with senses at the level of structure of the language. Furthermore, this research employed a descriptive study by analyzing the narrative texts. The result of the research described that the characters in the narrative texts are the entity’s profile of each active zones.